1992
DOI: 10.1161/01.atv.12.8.963
|View full text |Cite
|
Sign up to set email alerts
|

Flow affects development of intimal hyperplasia after arterial injury in rats.

Abstract: This study examined the effects of blood flow on intimal hyperplasia after balloon catheter injury of the rat common carotid artery. Flow was altered by ligation of the opposite common carotid artery (increased flow) or of the ipsilateral internal carotid artery (decreased flow). Blood flow decreased by 35% in the low-flow group and increased by 29% in the high-flow group. Similar changes in mean velocity were observed. Cross-sectional intimal area was significantly greater in the low-than the high-flow group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(70 citation statements)
references
References 20 publications
7
62
1
Order By: Relevance
“…29 Hemodynamic forces have been shown to modulate intimal hyperplasia (IH) at regions prone to atherogenesis 30 and to restenosis after percutaneous transluminal coronary angioplasty 31 by regulation of VSMC proliferation 32 and migration. 6 Kohler and Jawien 6 showed that early IH is increased when flow is reduced after balloon injury of the rat carotid artery. Their study suggests that enhanced flow attenuated VSMC migration more than proliferation, suggesting that VSMC migration affected more than smooth muscle cell growth by flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Hemodynamic forces have been shown to modulate intimal hyperplasia (IH) at regions prone to atherogenesis 30 and to restenosis after percutaneous transluminal coronary angioplasty 31 by regulation of VSMC proliferation 32 and migration. 6 Kohler and Jawien 6 showed that early IH is increased when flow is reduced after balloon injury of the rat carotid artery. Their study suggests that enhanced flow attenuated VSMC migration more than proliferation, suggesting that VSMC migration affected more than smooth muscle cell growth by flow.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] More specifically, reduced wall shear stress (WSS) has been shown to be associated with enhanced intimal lesion formation in atherosclerosis, 4 vascular grafts, 5 and balloon-injured vessels. 6 Conversely, relative elevations of blood flow and shear stress appear to have an atheroprotective role and inhibit intimal thickening after vascular injury. [7][8][9] Hemodynamic forces have been shown to modulate endothelial and vascular smooth muscle cell (VSMC) responses, which involve the induction of cytokines, such as platelet-derived growth factor (PDGF), basic fibroblast growth factor, and transforming growth factor-␤1 (TGF-␤1), 10,11 in addition to other mediators, such as nitric oxide, 7 tissue plasminogen activator, 12,13 and matrix metalloproteinases (MMPs), 1 4 involved in vascular remodeling.…”
mentioning
confidence: 99%
“…24 Changes in the fluid mechanical force from altered blood flow (shear stress) have direct effects on artery wall structure during growth and development 25 and on the progression of atherosclerosis and intimal hyperplasia. 26,27 An increase in shear stress or blood flow results in outward remodeling, which increases vessel size. In contrast, inward remodeling with reduced vessel size occurs in low-flow states with reduced shear stress.…”
Section: Hong Et Al Remodeling Of Intramyocardial Coronary Arteries 2063mentioning
confidence: 99%
“…[27][28][29] Therefore, we thought it would be worthwhile to evaluate the efficacy of HK gene delivery in preventing the vascular remodeling caused by permanent alteration in shear stress conditions. To this aim, we exploited the mouse model recently established by Kumar and Lindner, 20 in which disruption …”
Section: Discussionmentioning
confidence: 99%